The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12659/msm.918085
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life and the Use of Oral and Topical Nonsteroidal Anti-Inflammatory Drugs for Pericoronitis

Abstract: BackgroundPericoronitis is inflammation of the tissue surrounding a third molar, or wisdom tooth. This study aimed to evaluate the effects of oral and topical analgesic nonsteroidal anti-inflammatory drugs (NSAIDs) on oral health-related quality of life (OHQoL), in terms of oral health and lifestyle, in patients with symptomatic pericoronitis.Material/MethodsThe study included 60 patients who presented with pericoronitis and who did not undergo surgery within the following seven days. The patients were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Two ongoing RCTs were found (NCT03919942 and NCT03576105). Thus, we included seven RCTs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] in this systematic review. The flowchart of the search and screening of studies for the present review is shown in Figure 1 presents the flowchart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two ongoing RCTs were found (NCT03919942 and NCT03576105). Thus, we included seven RCTs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] in this systematic review. The flowchart of the search and screening of studies for the present review is shown in Figure 1 presents the flowchart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review included seven RCTs conducted in the Middle East, three from Turkey [ 12 , 13 , 14 ], 1 in Saudi Arabia [ 15 ] and 1 in Iran [ 16 ]. One study was performed in England [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, pain relief should be an integral part of pericoronitis treatment. The analgesics of choice should be nonsteroidal anti-inflammatory drugs (NSAIDs) [ 66 ]. Whether by administering local anesthesia or topical anesthesia, pain management is also an essential part of local treatment as it increases patient compliance during the procedure.…”
Section: Part A: Pericoronitis Evidence-based Therapymentioning
confidence: 99%